Sturge Weber Syndrome- A Rare Congenital Neuro-cutaneous Disease - Sultana, Wahida; Rita, Sufia Nasrin; Sadat, SM Anwar (Update Dental College Journal, 2016)
Sturge Weber Syndrome (SWS) or Encephalotrigeminal Angiomatosis is specifically a rare non hereditary congenital sporadic disorder of elusive etiology. It belongs to a group of disorders collectively known as the phakomatoses (motherspot diseases). It has a vast continuum of cutaneous, neurologic, ophthalmic and oral manifestations. It consists of congenital hamartomatous malformations that may affect the eye, skin, and central nervous system (CNS) at different times, characterized by the combination of venous angiomas of leptomeninges, face, jaws and oral soft tissues. The classic pathognomonic features of disease include angioma of the leptomeninges extending to cerebral cortex with ipsilateral angiomatous lesions, unilateral facial nevus after one division of trigeminal nerve and epileptic convulsions. The most characteristic oral manifestation is represented by gingival hemangiomatous lesion usually restricted to ipsilateral maxilla or mandible. We report a case of Sturge Weber Syndrome with its characteristic oral manifestations and review of relevant prevailing literature. Update Dent. Coll. j: 2015; 5 (2): 47-51